ORNITHODOROS MCLNTOSH IN THE STATE OF CHIAPAS MEXICO - MAZZOTTI, LUIS (Universidad Nacional Autónoma de México, Facultad Medicina, CD MEXICO, DF, MEX, 1950)
Some 85 birds of passerine spp were examined Plasmodium, Haemoproteus, and Leucocytozoon spp were found but were not characterized in detail Birds from Texcoco were generally parasitized, those from Xochi-milco were not
CIENC MEX
Keywords: ORNITHODOROS MCLNTOSH, CHIAPAS, MEXICO; MULTIDISCIPLINARIA; GEOLOGIA; GEOLOGIA REGIONAL